Problematika Penerapan Komunikasi Dua Arah Dalam Public Relations Digital Di Era Media Sosial - Fadhil Muhammad Husain (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to analyze the application of two-way communication in digital Public Relations practices in the social media era and identify the problems that contribute to its suboptimal implementation. This study used a descriptive quantitative approach with content analysis. Data were obtained from 10 posts on the Instagram account @Infosumbar within the past two months that had a high level of interaction, including audience comments and admin responses. The results show that audience interaction is high, but admin responses are still low, at 3.9%. This indicates that the communication is not yet dialogic and is still dominated by a one-way pattern. Based on James E. Grunig's concept of two-way communication, this condition indicates the lack of feedback, dialogic interaction, and ongoing relationships. The problems identified include low admin responses and suboptimal management of interactions with the audience.